Foreign Language Anxiety in Education - Neda Kianinezhad (JELITA, 2024)
Foreign Language Anxiety (FLA) poses a pervasive challenge for language learners venturing into the acquisition of a new language. Manifesting as heightened fear and anxiety, it significantly impacts the learning process. This comprehensive review aims to explore the origins, consequences, and aftermath of FLA, encompassing both traditional in-person learning and the virtual realm of online education, i.e., within the context of modern educational approaches, including distance and online learning. The narrative navigates the intricate interplay between anxiety and language acquisition, underscoring the pressing need for additional empirical evidence. The study emphasizes elucidating the origins and consequences of FLA and its impact on language learners in diverse educational settings. Highlighting the urgent requirement for empirical evidence, the review provides essential guidance for the development of holistic methods to nurture and support language learners as they progress toward linguistic proficiency. Finally, the review concludes by offering recommendations for future research endeavors pertaining to FLA.